Pemahaman Santriwati Terhadap Fiqih Puasa Wajib di Pondok Pesantren Zaadul Ma’ad Palembang - Aini, Huril; Mahyani, Aang (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyse female students’ understanding of the fiqh of obligatory fasting at the Zaadul Ma’ad Islamic Boarding School in Palembang. The study employs a descriptive qualitative approach, with female students selected through purposive sampling. Data collection was conducted through in-depth interviews to explore the female students’ conceptual understanding, observation of the fiqh learning process, and a documentary study of teaching materials and learning records. The data obtained were analysed using the Miles and Huberman model, which comprises the stages of data reduction, data presentation, and drawing conclusions. The research findings indicate that the majority of female students have understood the basic concepts of obligatory fasting fiqh, including its definition, purpose, obligatory conditions, intention, and the factors that invalidate fasting. However, their understanding of the distinction between factors that invalidate fasting and those that are merely disliked (makruh), as well as their understanding of contemporary issues in fasting fiqh, remains limited. These findings highlight the need for more contextual and practical fiqh education so that female students can relate the concepts of fasting fiqh to the real-life situations they face in their daily lives